Cadaveric Dissection in Relation to Problem‐Based Learning Case Sequencing: A Report of Medical Student Musculoskeletal Examination Performances and Self‐Confidence. Issue 6 (20th May 2019) - Thompson, Kristjan L.; Gendreau, Julian L.; Strickling, Jarred E.; Young, Henry E.
Abstract : Mercer University School of Medicine utilizes a problem‐based learning (PBL) curriculum for educating medical students in the basic clinical sciences. In 2014, an adjustment was piloted that enabled PBL cases to align with their corresponding cadaver dissection that reviewed the content of anatomy contained in the PBL cases. Faculty had the option of giving PBL cases in sequence with the cadaveric dissection schedule (sequential group) or maintaining PBL cases out of sequence with dissections (traditional group). During this adjustment, students' academic performances were compared. Students' perception of their own preparedness for cadaveric dissection, their perceived utility of the cadaver dissections, and free‐response comments were solicited via an online survey. There were no statistically significant differences when comparing student mean examination score values between the sequential and traditional groups on both multidisciplinary examinations (79.39 ± 7.63 vs. 79.88 ± 7.31, P  = 0.738) and gross anatomy questions alone (78.15 ± 10.31 vs. 79.98 ± 9.31, P  = 0.314). A statistically significant difference was found between the sequential group's and traditional group's (63% vs. 29%; P  = 0.005) self‐perceived preparedness for cadaveric dissections in the 2017 class. Analysis of free‐response comments found that students in the traditional group believed their performance in PBL group, participation in PBL group and examination performance was adversely affected when compared to students with the sequential schedule. This study provides evidence that cadaveric dissections scheduled in sequence with PBL cases can lead to increased student self‐confidence with learning anatomy but may not lead to improved examination scores.